2021
DOI: 10.3390/antibiotics11010047
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Poor Antibiotic and Antimicrobial Resistance Knowledge and Inappropriate Antibiotic Use in the General Population Are Modified by Age

Abstract: Objectives: Understanding factors influencing inappropriate antibiotic use can guide the design of interventions to improve antibiotic practices and reduce antimicrobial resistance (AMR). Methods: A nationally representative cross-sectional survey (N = 2004) was conducted between November 2020 and January 2021. Knowledge of antibiotic use and AMR using the World Health Organization’s Multi-Country AMR Survey questionnaire, and antibiotic practices were examined. Multivariable logistic regression was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
3
21
0
Order By: Relevance
“…Respondents over 40 years old or retired, proactive, confident in practitioner about antibiotics, and having a high level of knowledge about antibiotics, practiced less antibiotic misuse. These results are in agreement with those of Guo et al (2022) who observed that adults over 50 years old with poor knowledge of antibiotic use had a 3× increased odds of inappropriate antibiotic use in adults aged ≥ 50 years [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Respondents over 40 years old or retired, proactive, confident in practitioner about antibiotics, and having a high level of knowledge about antibiotics, practiced less antibiotic misuse. These results are in agreement with those of Guo et al (2022) who observed that adults over 50 years old with poor knowledge of antibiotic use had a 3× increased odds of inappropriate antibiotic use in adults aged ≥ 50 years [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to Eurobarometer data, 39% of French took antibiotics at least once in 2016 [ 54 ]. Public knowledge, attitudes, and beliefs about antibiotics were strong determinants of antibiotic misuse [ 55 ]. The main part of the French general population (84%) knew that the unnecessary use of antibiotics makes them become ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…A more nuanced approach utilising a combination of strategies that target different sub-populations is evidently necessary to address knowledge and practice gaps, and improve antibiotic stewardship in the community. This is further supported by a previous study reporting the modifying effects of age on the association between poor knowledge of antibiotic use and AMR, respectively, and poor antibiotic practices, highlighting the need to tailor educational interventions by age [ 14 ].…”
Section: Introductionsupporting
confidence: 72%
“…This suggests that for the purposes of disseminating health information, Internet-based platforms are less effective for older adults with LL-HIO due to the much lower Internet utilisation rates and barriers to utilise Internet-based information. Instead, there is a need for physical, social and healthcare touchpoints, with whom they have close and sustained relationships, to actively reach out to and educate this sub-population, using traditional non-Internet-based modalities such as posters or pamphlets and annual campaigns on appropriate antibiotic use to improve antibiotic practices [ 14 ]. Similar findings on the relationship between HIO, health information efficacy, and community participation in good preventive health behaviours have been previously reported, highlighting the importance of working with non-traditional communication platforms to reach out to specific segments of the community [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation